PENGARUH LIKUIDITAS, PROFITABILITAS DAN PERTUMBUHAN PENJUALAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Anggela, - Fellicia (EKONOMIA, 2019)
By taking the title of Influence Liquidity, Profitability, and sales growth on stock prices in the sub-sector companies Property listed on the Indonesia Stock Exchange (BEI). The data used in this study is secondary data in the form of financial statements of 2010-2014 obtained from the official website of Indonesia Stock Exchange namely www.idx.co.id.This study uses 11 samples companies that meet the criteria of testing. So that the amount of data to be analyzed amounted to 55. Before performing the data analysis techniques, first tested the classical assumption. Hypothesis testing using multiple linear regression test by f test, and t test with SPSS 16.0 for Windows software.Â The result of simultaneous research shows that variable of current ratio, return on equity, and penjulan growth have no significant effect to stock price, where the value of Fcount <Ftable or Fcount 0.160 < Ftable 2.79. Partially indicate that variable of Current Ratio have no significant effect to stock price, where Tcount < Ttable or Tcount = 0,02 < Ttable = 2,005. Return On Equity has no significant effect on stock price, where tcount < Ttable or Tcount = -1,444 < Ttable = 2,005. The growth of sales has no significant effect on stock prices, where the value of Tcount < Ttable or Tcount = 0,310 < Ttable 2,005.